numerical analysis defects, thermolysis, infinite cylindrical ceramic moulding - Camerlengo, Alejandro Livio (Universiti Putra Malaysia Press, 1999)
Some aspects of the meridional circulation of the atmosphere are considered. It is corroborated that: (a) the existence of the meridional circulation is primarily determined by the eddies, and (b) that the meridional circulation is set up by surface friction in the zone of the westerlies in the case of strong baroclinicity.